Między sceną a dziełem. O reformującej roli dramatów muzycznych Richarda Wagnera - Kozłowski, Krzysztof (Wydawnictwo Naukowe UAM, 2008)
In Between stage and work of literature. In the reforming role of Richard Wagner's musical dramas the author tries to show that musical dramas of the German composer were actually important artistic events which could contribute to the understanding of the complex relations between the stage and the musical drama as preserved in the score. The lack of the unequivocally outlined conception of the work - incomplete at different levels and unspecified in its many aspects - gave an impulse to numerous stage experiments which appeared to be of significance just from the point of view of the history of the theatre. And so the history of staging Wagner's dramas became a part of its history; Adolphe Appia, a Swiss reformer of the theatre was one of the first to find this regularity and tried to present it on stage using all the historical changeability of the latter.
Between stage and work of literature. In the reforming role of Richard Wagner's musical dramas